2014
DOI: 10.1042/bst20140025
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of asymmetric RAF dimer activation

Abstract: Protein phosphorylation is one of the most common post-translational modifications in cell regulatory mechanisms. Dimerization plays also a crucial role in the kinase activity of many kinases, including RAF, CDK2 (cyclin-dependent kinase 2) and EGFR (epidermal growth factor receptor), with heterodimers often being the most active forms. However, the structural and mechanistic details of how phosphorylation affects the activity of homo- and hetero-dimers are largely unknown. Experimentally, synthesizing protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 48 publications
2
25
0
Order By: Relevance
“…Total atom numbers for each system including water molecules are reported in Table 1. Systems were prepared for MD simulation as described in our previous papers using also similar NPT MD studies [3840] of larger amyloid peptides such as Alzheimer’s amyloid-beta (Aβ, [4143]) or human amylin (hIAPP, [44]).…”
Section: Methodsmentioning
confidence: 99%
“…Total atom numbers for each system including water molecules are reported in Table 1. Systems were prepared for MD simulation as described in our previous papers using also similar NPT MD studies [3840] of larger amyloid peptides such as Alzheimer’s amyloid-beta (Aβ, [4143]) or human amylin (hIAPP, [44]).…”
Section: Methodsmentioning
confidence: 99%
“…Intriguingly, these salt bridges are primarily interprotomer salt bridges, which are formed between the NtA motif and positive residues located either upstream of the NtA motif or at the C‐terminal end of the αC‐helix, the orientation of which plays an important role in kinase activation 12a, 13…”
mentioning
confidence: 99%
“…The proximity of the N region to the dimer interface has been noted (20,66,67). Molecular dynamic simulations have suggested that the phosphorylation of the N region expands this dimer interface, in part by enhancing potential electrostatic interactions between the N region and the opposite RKTR motif that lies within the ␣C helix of the opposite Raf monomer (68,69). That study predicted structural changes within the Raf dimer.…”
Section: Discussionmentioning
confidence: 83%